GRP-047 CREx and ORIONÆ Analysis in an Hospital Pharmacy: A Six-Month Review. (12th March 2013) - Pichard, C; Roussel, F; Debrix, I; Baud-Camus, F
Abstract : Background: Prevention of medication errors has led to improved safety of the drug use system. Experience feedback committees (Comités de Retour d'Expérience, CREx), in particular, can help health professionals to improve the quality and safety of drugs management. Purpose: To set up a CREx in our pharmacy, in order to record, analyse and correct precursor events. Materials and Methods: Medication errors are collected on a report form. Once a month, these errors are reported to CREx and the staff select the event that will be discussed in the next CREx meeting. The ORION method, based on experience acquired in aeronautics, was selected to analyse how the CREx should operate. The systemic analysis is divided into 5 steps, performed by a pilot trained in the method and presented during CREx. The five steps are: collect the data, rebuild a chronology of facts, identify any gaps, contributing and influential factors, propose corrective measures and write the analysis report. Results: From April to September 2012, 61 dysfunctions were reported. 19 were actual and 42 were potential errors. Among these errors, 47.5% related to prescription, 21% to dispensing, 21% to inventory management, 7% to administration, 1.7% to validation and 1.7% to preparation. Five of these errors were analysed in CREx (ORION method). Ten corrective measures were proposed, 6 of which were actually implemented. We noted an increase in the number of dysfunctions reported, from 4 dysfunctions reported in April to 22 in September. Conclusions: CREx is well established in our pharmacy, taking place once a month, with representatives of all pharmacy staff. After six months, CREx has enabled 6 corrective measures to be implemented (creation or modification of procedures, modification of medicines management, etc.). It has also enabled pharmacy staff to understand the importance of reporting and analysing medication errors. CREx is thus an approach to sustain in order to improve the safety of the drugs use system. No conflict of interest.